Relationship Factors Physical Environment and Behavior house Respondents with incidence of Dengue Hemorrhagic Fever in Depok 2016 - Fathinah Ranggauni; Nuning Maria Kiptiyah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
AbstractDepok City is one of the endemic areas of dengue disease in Indonesia. An increase and spread of dengue cases was likely caused by the high mobility of the population, urban development, climate change, changes in population density and distribution. This research is an analytic study with case control design. This study found that in bivariate analysis, the variables associated with the incidence of dengue in the city of Depok are variable lighting (OR = 2.857, 95% CI = 1.179 to 7.175), variable cleaning TPA (OR = 2.210, 95% CI = 0.972 to 5.103), variable educational level (OR = 24.375 (95% CI = 3.540 to 1030.606). On multivariate analysis, the home environment variables that individuals with home lighting ineligible risk of 3.369 (95% CI: 1.418 to 8.005) compared to individuals exposed to dengue home lighting qualify as controlled by confounding variables, namely the habit of cleaning water reservoirs and jobs. On multivariate analysis, behavioral variables respondent is an individual who cleans water reservoirs are not routinely <1 time a week are at risk of 3.293 (95% CI: 1.321 to 8.212) DHF compared with individuals who have  the  habit  of  cleaning  water  reservoirs  regularly  after  confounding  variables  are  controlled  by environmental conditions and education of home lighting. For Depok City Health Department inspection home lighting conditions and larvae regularly, fogging and improve health promotion to respondents on how to prevent dengue by conducting 3M plus especially on variable bathtub drain in order to suppress the incidence of dengue in the working area. For respondents in order to join and participate in efforts to Mosquito Nest Eradication of Dengue Hemorrhagic Fever (PSN-DBD).